PEMETAAN KUALITAS AIR IRIGASI PERTANIAN DI LERENG TIMUR LAUT GUNUNG LAWU, NGAWI - SAIFUDIN, ALIF ([Yogyakarta] : Universitas Gadjah Mada, 2014)
As one of the most important input for agriculture activity, water resource still become a mainstay to supply water crop requirements. Increasing population number and industrial rapid growth in developing country may have worse impact on water resources. Water characteristic such as physical, chemical and biologal parameters are the key to determine and achieving good water quality. This research was conducted to determine water quality level for irrigation in the north east slope of Lawu Mount and to mapping water quality area. Determination of sample point locations based on altitude and water source existence. Water quality sample analyze were conducted in Laboratory of Environmental Health and Contagion Eradicating Agency Yogyakarta, Hidrology and Water Quality Laboratory Geographical Faculty UGM and General Soil Laboratory Agriculture Faculty UGM. The result shows that fecal coliform parameter was exceeding quality standard according to Government Regulation Number 82 in 2001 concerning water quality. Most coliform contamination occur in Ketonggo and Dadapan River. Water quality decrease caused by pollutan indigenous to environmental condition and antropogenic activities. The result on water quality were evaluated using the STORET system shows that water at good quality condition or minor pollute status.